Up-Skilling and Re-Skilling Teachers on Vocational High School with Industry Needs - Fitri Nur Mahmudah; Sulistio Mukti Cahyono; Arif Susanto; Suhendar Suhendar; Khieng Channa (Journal of Vocational Education Studies, 2021)
The development era demands the skills of teachers to meet needs and adjust. This means that the teacher's ability to upgrade is needed. The objectives of this study were (1) to determine the up-skilling that must be done by vocational school teachers with world-standard work era 4.0; and (2) knowing the concrete steps that must be taken by vocational schools teachers in re-skilling the world-standard work era 4.0. The method used in this research is qualitative with a case study approach. The technique of determining participants using purposive sampling. Participants in this study were vocational school teachers, vocational schools service branches, and widyaiswara. Data collection techniques using structured interviews by preparing interview guidelines. Data analysis using Creswell case study data analysis model, namely (1) data management; (2) memoing; (3) exposure; (4) classification; and (5) interpretation. Data analysis in the study was carried out with the assistance of Software Altas. ti version 8. The results of this study are (1) up-skilling of industrial standard vocational school teachers in the era of 4.0 needs to be done with three components, namely (a) develop new skills; (b) time-to-hire; (c) competency assessment. Meanwhile, (2) re-skilling of vocational schools teachers with industrial standard era 4.0 consists of three components, namely (a) intelligent digital tools; (b) create new tasks and occupations; and (c) coaching programs. This implication can be used for widyaiswara in providing training to vocational school teachers.